2015
DOI: 10.1007/s40333-015-0129-6
|View full text |Cite
|
Sign up to set email alerts
|

Surface energy and water vapor fluxes observed on a megadune in the Badain Jaran Desert, China

Abstract: The Badain Jaran Desert is the second-largest area of shifting sands in China. Our first measurements of the energy components and water vapor fluxes on a megadune using eddy covariance technology were taken from April 2012 to April 2013. The results indicate that the longwave and shortwave radiative fluxes exhibited large fluctuations and seasonal dynamics. The total radiative energy loss by longwave and shortwave radiation was greater on the megadune than from other underlying surfaces. The radiation partiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…Such results point out the significantly greater ability of lakes to store energy as compared to dunes. Thus, under the unique dune-lake landscape of BJD, the difference in net radiation will inevitably lead to uneven heat distribution [47][48][49][50]. Consequently, the local air circulation between lakes and megadunes will affect the spatial distribution pattern of heat resource by way of air movements [19].…”
Section: Reason For the Warm Island Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Such results point out the significantly greater ability of lakes to store energy as compared to dunes. Thus, under the unique dune-lake landscape of BJD, the difference in net radiation will inevitably lead to uneven heat distribution [47][48][49][50]. Consequently, the local air circulation between lakes and megadunes will affect the spatial distribution pattern of heat resource by way of air movements [19].…”
Section: Reason For the Warm Island Effectmentioning
confidence: 99%
“…Such results point out the significantly greater ability of lakes to store energy as compared to dunes. Thus, under the unique dune-lake landscape of BJD, the difference in net radiation will inevitably lead to uneven heat distribution [47][48][49][50].…”
Section: Reason For the Warm Island Effectmentioning
confidence: 99%
“…Hu et al . () found that the strongest winds in the hinterland of the Badain Jaran Desert during the day and at night were 9.53 and 8.78 m/s, respectively, which suggested that the transport of aeolian sand by wind was possible. Moreover, the lake sediments are composed largely by sand and had moderately skewed grain size distribution (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…No surface flow is observed because of the high ratio between evaporation and precipitation rates (Ma et al ., ; Dong et al ., ). Mean wind speed increases significantly from 3.7 m/s in the south to 4.6 m/s in the north, with the strongest winds occurring in spring (Hu et al ., ). The prevailing wind direction is northwest over the year, owing to the influence of winter monsoon from the Siberian High Pressure System (Hu and Yang, ).…”
Section: Study Areamentioning
confidence: 97%
“…The average vertical deflection in the wind direction was -1.1°. The frequency response correction (Moncrieff et al, 2005), sonic temperature correction (Van Dijk et al, 2004) and density fluctuation correction (WPL-correction) (Webb et al, 1980) were applied (Hu et al, 2015). We also carried out a turbulence stationarity test (Foken and Wichura, 1996) and an overall turbulence characteristic test, evaluated the quality of data and divided the data according to the quality level.…”
Section: Data Quality Control and Flux Footprint Analysis Of Ecmentioning
confidence: 99%